Structural and Molecular Determinants of Membrane Binding by the HIV-1 Matrix Protein. Issue 8 (24th April 2016) - Mercredi, Peter Y.; Bucca, Nadine; Loeliger, Burk; Gaines, Christy R.; Mehta, Mansi; Bhargava, Pallavi; Tedbury, Philip R.; Charlier, Landry; Floquet, Nicolas; Muriaux, Delphine; Favard, Cyril; Sanders, Charles R.; et al.
Abstract: Assembly of HIV-1 particles is initiated by the trafficking of viral Gag polyproteins from the cytoplasm to the plasma membrane, where they co-localize and bud to form immature particles. Membrane targeting is mediated by the N-terminally myristoylated matrix (MA) domain of Gag and is dependent on the plasma membrane marker phosphatidylinositol-4, 5-bisphosphate [PI(4, 5)P2 ]. Recent studies revealed that PI(4, 5)P2 molecules containing truncated acyl chains [tr-PI(4, 5)P2 ] are capable of binding MA in an "extended lipid" conformation and promoting myristoyl exposure. Here we report that tr-PI(4, 5)P2 molecules also readily bind to non-membrane proteins, including HIV-1 capsid, which prompted us to re-examine MA–PI(4, 5)P2 interactions using native lipids and membrane mimetic liposomes and bicelles. Liposome binding trends observed using a recently developed NMR approach paralleled results of flotation assays, although the affinities measured under the equilibrium conditions of NMR experiments were significantly higher. Native PI(4, 5)P2 enhanced MA binding to liposomes designed to mimic non-raft-like regions of the membrane, suggesting the possibility that binding of the protein to disordered domains may precede Gag association with, or nucleation of, rafts. Studies with bicelles revealed a subset of surface and myr-associated MA residues that are sensitive to native PI(4, 5)P2, but cleft residues that interact with the 2′-acyl chains of tr-PI(4, 5)P2 molecules in aqueous solution were insensitive to native PI(4, 5)P2 in bicelles. Our findings call to question extended-lipid MA:membrane binding models, and instead support a model put forward from coarse-grained simulations indicating that binding is mediated predominantly by dynamic, electrostatic interactions between conserved basic residues of MA and multiple PI(4, 5)P2 and phosphatidylserine molecules. Graphical abstract: Highlights: The influences of lipid constituents on membrane binding by HIV-1 MA were determined. NMR results differed from those obtained by non-equilibrium flotation assays. The structural basis for PI(4, 5)P2 -dependent membrane targeting was re-examined. Native PI(4, 5)P2 does not bind MA in a predicted "extended lipid" conformation. MA may bind non-raft regions and recruit raft-like constituents during assembly.